Executive Committee Minutes 2013-01-31 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 1/17 approved. Chair Report. Provost Report. Questions from SDS. Charges for academic use of the GMC. Change to GE Area B accounting – referred back to committee. Faculty Governance Assigned Time for '12 – '13 approved. Vice Chair Report. Vice President of Administrative and Finance Report. Question for the Chief Student Affairs Officer. APC Report. EPC Report. FSAC Report. SAC Report. Associated Students Report. Senate agenda approved.